Optimal Thresholding of Predictors in Mineral Prospectivity Analysis - Baddeley, Adrian; Brown, Warick; Milne, Robin K; Nair, Gopalan; Rakshit, Suman; Lawrence, Tom; Phatak, Aloke; Fu, Shih Ching (Kluwer Academic/Plenum Publishers, 2020)
© 2020, International Association for Mathematical Geosciences.